FLOOD RISK ANALYSIS OF EDU LOCAL GOVERNMENT AREA (KWARA STATE, NIGERIA) - Emmanuel Oriola; Cynthia Chibuike (Geography, Environment, Sustainability, 2016)
This study examines flood risk propensity of communities in Edu Local GovernmentArea of Kwara state, with a view to classifying the area into risk zones for better and proper management of the environment for the sustainable living of the people. The three administrative districts of Edu Local Government area were identified as pragmatic areas for the study. In each of the districts, Geographical Information System data capture and analytical tool were used to harvest and treat the data for subsequent interpretation. The coordinates of various locations of interest were taken, contour and slope maps of the area were generated to produce flood risk map for the area. The results revealed three distinct risk zones; High, Moderate, and low-risk areas. Three settlements fall into a low-risk area with elevations above 196 m, two settlements located at between 110 m and 196 m are within moderate risk zone and six settlements in High-risk area with elevations below 110 m. This paper concludes that the people of the riverine communities in Edu LGA are culturally attached to the environment. The study, therefore, recommends public enlightenment on the trend in climate and weather about the flood and its implications, environmental education and then resettlement of these communities. When and where resettlement scheme proves very difficult due to strong cultural attachment, flood prevention mechanism via engineering construction such as dykes, embankments and ditches should be adopted.